Transition Away from School: A Framework to Support Professional Understandings - Gillie, Sarah (International Journal of Educational and Life Transitions, 2023)
The numbers of children with ‘special educational needs’ deregistering from UK schools to begin home-education has been increasing. This article is based on findings from a survey of 93 families of such children in England, Scotland and Wales conducted as part of a study that investigated the processes leading them to home educate. The research question was: What circumstances inform the transitions of families to and within home-education? Home-education is often portrayed as a rejection of social norms, a perception that can result in parents’ feelings of exclusion even when children are no longer enrolled at school.The research revealed often protracted, cumulative, and frequently traumatic sequences of events pushing families to home educate. The study’s framework blends Bronfenbrenner’s bioecological system’s model with Turner’s liminal theory and stages of social drama to analyse these relationships and processes. Staged circumstances reflect aspects of metaphorical ritual, where actors transition to, through and beyond liminality, supported by others with similar experiences.The study’s original framework provides a lens for educators to consider families’ experiences. This can support them to meet existing institutional, professional and ethical responsibilities. As well as its potential to scaffold practice for individual educators, children and families, the framework has implications for teacher education, and the implementation and development of policy.
Keywords: educational transition; home education; inclusion; parent partnership; school deregistration; teacher education